AI Integration in IT Education: Challenges, Opportunities, and Future Directions - Ortega-Dela Cruz, Ruth A.; Dela Cruz, Ramiro Z. (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
The rapid advancement of artificial intelligence (AI) has generated significant interest within the educational sector, particularly in information technology (IT) education. This study explored the current challenges, opportunities, and future directions of AI in IT education in the Philippines, a nation working to enhance its educational system in the face of digital transformation. Through a survey research design, data was collected from IT students, and educators. Results highlight the key challenges such as inadequate infrastructure, limited resources, gaps in AI literacy, and concerns around ethics and data privacy. Despite these challenges, opportunities such as personalized learning, streamlined administrative processes through task automation, and advancements in research through improved data collection, processing, and analysis provide hope for the integration of AI in IT curricula. Moving forward, efforts should focus on curriculum development, supportive policy frameworks, and continuous research to leverage AI's benefits in IT education. With robust government support, industry collaboration, and ethical AI practices, the Philippines can effectively use AI to transform IT education and equip students for a tech-driven future.